1989
DOI: 10.1037/1040-3590.1.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Toward the validation of the California Therapeutic Alliance Rating System.

Abstract: The California Therapeutic Alliance Rating System, CALTARS, was used by judges to rate four therapy sessions for each of 52 subjects treated in brief dynamic psychotherapy for pathological grief. A principal-components analysis provided support for the theoretically proposed domains of alliance. The interrater reliability at the treatment level was satisfactory for the five component-based scales. As hypothesized, scores reflecting positive contribution to the alliance were positively related to educational at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(143 citation statements)
references
References 25 publications
3
134
0
6
Order By: Relevance
“…It assesses the patients' capability of observing their reactions, of working actively with the therapist's remarks and to solve problems. According to this concept a higher capability of patients to establish the working alliance has produced the most significant outcomes in this study, what has been already observed by other authors 59 who reported a significant correlation between the working alliance (PWC) and the improvement in the symptomatology.…”
Section: Impact Of the Therapeutic Alliance On Psychotherapy Outcomessupporting
confidence: 75%
“…It assesses the patients' capability of observing their reactions, of working actively with the therapist's remarks and to solve problems. According to this concept a higher capability of patients to establish the working alliance has produced the most significant outcomes in this study, what has been already observed by other authors 59 who reported a significant correlation between the working alliance (PWC) and the improvement in the symptomatology.…”
Section: Impact Of the Therapeutic Alliance On Psychotherapy Outcomessupporting
confidence: 75%
“…A potential confounding effect of a process variable not assessed in the study was suggested by Marmar and colleagues (Marmar et al, 1986;Marmar et al, 1989). A client's discontent with their early treatment progress might be reflected in poorer client alliance ratings more indicative of the dissatisfaction than of the relationship.…”
Section: Discussionmentioning
confidence: 92%
“…It appears that the B-L RI assesses primarily the first of Gaston's dimensions, whereas the VTAS assesses primarily the other dimensions. However, there is disagreement about the extent to which these dimensions of the therapeutic relationship can be empirically discriminated (e.g., Hartley & Strupp, 1983;Hatcher & Barends, 1996;Marmar, Weiss, & Gaston, 1989).…”
mentioning
confidence: 99%